Osteocutaneous radial forearm free flap in nonmandible head and neck reconstruction. Issue 9 (4th July 2017) - Ahmad, Faisal I.; Means, Casey; Labby, Alex B.; Troob, Scott H.; Gonzalez, Javier D.; Kim, Michael M.; Li, Ryan J.; Wax, Mark K.
Abstract: Background: The osteocutaneous radial forearm free flap (RFFF) is a versatile flap primarily used to reconstruct composite defects involving the mandible. The purpose of this study was to describe our experience with this flap for nonmandible reconstruction. Methods: All patients undergoing nonmandible osseous reconstruction with free‐tissue transfer were reviewed. Patients with osteocutaneous RFFF reconstructions were evaluated. The retrospective review of all osteocutaneous RFFFs was performed from 1998 to 2014. Results: One hundred forty‐two nonmandible osseous reconstructions were performed. Twenty‐five patients underwent nonmandible osteocutaneous RFFF reconstruction. Eleven patients failed previous nonmicrovascular reconstruction. Reconstruction was for defects of the: palatomaxillary complex (n = 15), orbitomaxillary complex (n = 4), nasomaxillary complex (n = 4), larynx (n = 1), and clavicle (n = 1). There were no flap compromises. Postoperative complications included: 2 partial intraoral dehiscences; 1 recipient‐site infection; and 1 seroma. Eight reconstructions required secondary procedures to improve functional and/or cosmetic outcomes. Conclusion: The osteocutaneous RFFF is a robust flap that can be used to reconstruct composite defects involving bone and soft‐tissue beyond the mandible.